Tracing past extreme floods on an alluvial fan using geophysical surveying - Arboleda‐Zapata, Mauricio; Guillemoteau, Julien; Lucía, Ana; Eberle, Joachim; Tronicke, Jens; Korup, Oliver (Earth surface processes and landforms, 2023)
Summary Sedimentary units in alluvial fans may record gradual transport and deposition during multiple floods or sediment‐laden flows or, conversely, during few catastrophic events. While outcrops are a valuable source of direct information to constrain past geomorphic and hydrologic processes, such exposures are scarce, especially along aggrading rivers or those that have been subject to recent catastrophic sedimentation. In this context, near‐surface geophysical techniques can constrain the dimensions, internal architecture, composition, and petrophysical properties of different sedimentary units. We consider the Grimmbach alluvial fan in the cuesta landscape of southwestern Germany, which was heavily impacted by sediment and wood loads during a flash flood in 2016; published radiocarbon dates indicate that at least three floods similar to the one in 2016 may have occurred since the 17th century. To test whether and to which detail near‐surface geophysics might reveal the sedimentary legacy of these floods, we survey the Grimmbach alluvial fan using detailed topographic data and geophysical imaging based on electromagnetic induction, electrical resistivity tomography (ERT), and ground‐penetrating radar. Our geophysical results indicate former channel courses and two coarse bar deposits up to 3 m below the surface, which are comparable with the more extensive bar deposits of the 2016 flood. From the ERT models, we interpret coarse, up to 5 m thick, gravel lag overlying bedrock at a maximum depth of 10 m. Our geophysical results also highlight patches of finer materials derived from gradual sedimentation and soil development. Overall, our results show that the Grimmbach alluvial fan may have formed and reshaped during catastrophic flows, which likely caused channel avulsions. Our findings point to the need to reconsider flash flood and debris‐flow hazards in similar headwaters and fans of this seemingly quiescent cuesta landscape in southern Germany. We perform a geophysical study in a small alluvial fan in the cuesta landscape of southwestern Germany. Our results reveal sedimentary structures pointing to past catastrophic events. Our findings ask for reconsidering flash flood and debris‐flow hazards in many similar headwaters and fans of this cuesta landscape.